Flipped classroom as a methodology for acquiring skills in sustainability in the subject production management: an assessment of the students - Martín-Peña, María Luz; Díaz-Garrido, Eloísa; Sánchez-López, José María; García-Magro, Cristina (Journal of Management and Business Education, 2023)
The need to integrate competences aligned with the Sustainable Development Goals (SDGs) into higher education curricula has gained considerable attention in recent years. While the literature shows an increase in research on this topic, there remains a scarcity of papers addressing effective strategies to foster students' environmental sustainability competencies and skills, through active pedagogical methods. A promising avenue to achieve this goal is the adoption of the Flipped Classroom methodology. This approach has proven its ability to guide students towards reflection and critical thinking, making it a good tool for promoting sustainability awareness. An experience of educational innovation is presented that develops SDG 12 "Guarantee sustainable consumption and production patterns", and SDG 9 "Industry, innovation and infrastructures", in the subject Production Management, with the aim of achieving the competence "environmental awareness". From the perspective of the students, an evaluation of the educational experience is presented. The results show the success of the Flipped Classroom methodology in providing students with a holistic understanding of the principles of sustainable development and their application through the SDGs within their academic trajectory. In particular, this approach provides them with the skills and aptitudes to promote sustainability.